2020
DOI: 10.1002/pds.5065
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban was found to be noninferior to warfarin in routine clinical care: A retrospective noninferiority cohort replication study

Abstract: Purpose: To compare the effectiveness and safety of a drug in daily practice with the outcomes of a target non-inferiority trial by rigorously mimickingin an observational study the trial's design features. Methods: This cohort study was conducted using the British Clinical Practice Research Datalink (CPRD) to emulate the ROCKET AF (Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation) trial. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred and fifteen studies (58%) completely reported how the target trial protocol was emulated. Eighty-seven studies (44%) provided both the protocol of the target trial and described how it was emulated (Table 2). The following items of the emulation were frequently reported: eligibility criteria (193 [97%]), treatment strategies (191 [96%]), assignment procedures (173 [87%]), primary outcome (196 [98%]), the follow-up period (186 [93%]), a causal contrast (146 [73%], and an analysis plan (194 [97%]) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from large observational registries can be used to guide clinical decision-making by emulating a clinical trial. [9][10][11] In this study, we used data from 2 MS registries to evaluate the clinical noninferiority of rituximab compared with ocrelizumab in the treatment of patients with relapsingremitting MS. 12,13…”
mentioning
confidence: 99%